ANALISIS EKONOMI SOSIAL KEBERADAAN MINI MARKET DI KOTA MAKASSAR (Studi Kasus pada Mini Market PT. Sumber Alfaria Trijaya) - Misbahuddin Misbahuddin (AkMen JURNAL ILMIAH, 2013)
The proliferation of mini-market in Makassar received varied responses, ranging from the mini market continued to support growth, until the termination / delay permits the establishment of a new mini mini Alfamart particular. Besides the proliferation of mini-issues that have been beyond the limit, mini-competition between the issue also drew attention to serious enough, it can be seen from the concentration of several mini in one location so it may be necessary to see how consumers respond to the minimarket, and how consumers in determining the minimarket in the shop to meet their needs. Therefore, it is considered necessary conduct studies or research on the social and economic impact on the community response to the presence of the existing mini market in Makassar over the years, through a survey study of existence Minimarket Alfamart and Consumer Behavior in Makassar.